Economía y urgencia fiscal: los asientos hacendísticos del Consulado de Lima en la segunda mitad del siglo XVII - Jímenez Jímenez, Ismael (2016)
The unpromising state of the colonial Peruvian economy, where prices were rising and productivity was at a standstill, led to a great slowdown in the tributary income of the Monarchy. In the face of this situation, the best solution to increase economic activity and swell the coffers of the Royal Tax Office was to hand over tax collection to Lima’s Consulado de Comercio. From the 1660s through the beginning of the eighteenth century, there was constant negotiation in Peru between the consigner, the Crown, and the consignees, the merchants.